UNICEF ESARO guidance on Sign Language for Deaf Children’s Education and its Use in Accessible Digital Teaching & Learning Materials | UNICEF Eastern and Southern Africa - and Auma Obura, Georgine (UNICEF, 2021)
While we are witnessing a growing awareness among policy makers in the ESA region of the need to make education more inclusive especially for children with disabilities, data on children with disabilities, policies and funding to support their access to quality education remain major issues and will be bottlenecks to progress towards SDG4. As part of the United Nations Partnership for the Rights of Persons with Disabilities (UNPRPD) multi-country initiative, “Promoting Inclusive Education through Accessible Digital Textbooks”, UNICEF ESARO wishes to support efforts to improve schooling and learning opportunities for children with hearing disabilities by providing guidance on the use of sign languages. The document seeks to improve inclusive education for deaf learners by advancing: The use and official recognition of national sign languages as the first and most accessible natural languages. Sign language supports deaf children in their linguistic, cognitive, and social-emotional development. Consistent use of national sign languages in the development of accessible digital teaching and learning materials for deaf children. Although the guidance note focuses primarily on countries in the Eastern and Southern Africa (ESA) region, it can also help inform efforts to develop accessible digital teaching and learning materials in other regions.
Keywords: Org:eKitabu